Caenorhabditis elegans as an Infection Model for Pathogenic Mold and Dimorphic Fungi: Applications and Challenges - Ahamefule, Chukwuemeka Samson; Ezeuduji, Blessing C.; Ogbonna, James C.; Moneke, Anene N.; Ike, Anthony C.; Jin, Cheng; Wang, Bin; Fang, Wenxia (Frontiers in Cellular and Infection Microbiology, 2021)
The threat burden from pathogenic fungi is universal and increasing with the alarming high mortality and morbidity rates from invasive fungal infections. Understanding the virulence factors of these fungi, screening effective antifungal agents and exploring appropriate treatment approaches in in vivo modelling organisms are vital research projects for controlling mycoses. Caenorhabditis elegans has been proven to be a veritable tool in the studies of most clinically relevant dimorphic fungi, helping to identify a number of virulence factors, immune-regulators and screen effective antifungal agents without cytotoxic effect. However, little has been achieved and reported with regard to pathogenic filamentous fungi (moulds) in the nematode model. In this review we have summarized the enormous breakthrough of applying C. elegans infection model for dimorphic fungi studies and the very little reports for filamentous fungi. We have also identified and discussed the challenges in C. elegans-moulds modelling applications as well as the possible approaches to conquer these challenges from our practical knowledge in C. elegans-A. fumigatus model.